Hubble Tarantula Treasury Project: II. The star-formation history of the starburst region NGC 2070 in 30 Doradus - Cignoni, Michele; Gouliermis, Dimitrios A.; Grebel, Eva K.; Zeidler, Peter (The astrophysical journal, 2015)
We present a study of the recent star formation (SF) of 30 Doradus in the Large Magellanic Cloud (LMC) using the panchromatic imaging survey Hubble Tarantula Treasury Project. In this paper we focus on the stars within 20 pc of the center of 30 Doradus, the starburst region NGC 2070. We recovered the SF history by comparing deep optical and near-infrared color-magnitude diagrams (CMDs) with state-of-the-art synthetic CMDs generated with the latest PAdova and TRieste Stellar Evolution Code (PARSEC) models, which include all stellar phases from pre-main-sequence to post-main-sequence. For the first time in this region we are able to measure the SF using intermediate- and low-mass stars simultaneously. Our results suggest that NGC 2070 experienced prolonged activity. In particular, we find that the SF in the region (1) exceeded the average LMC rate ≈ 20 Myr ago, (2) accelerated dramatically ≈ 7 Myr ago, and (3) reached a peak value 1-3 Myr ago. We did not find significant deviations from a Kroupa initial mass function down to ##IMG## [http://ej.iop.org/images/0004-637X/811/2/76/apj519047ieqn1.gif] $0.5\;M_ødot $ . The average internal reddening ##IMG## [http://ej.iop.org/images/0004-637X/811/2/76/apj519047ieqn2.gif] $E(B-V)$ is found to be between 0.3 and 0.4 mag.